IMPLEMENTASI ALAT TEPAT GUNA HASIL HIBAH BI UNTUK MENINGKATKAN KESEHATERAAN MASYARAKAT - Bonar BJ Napitupulu; Francisca Sesri G; Dwi Ferdyatmoko C.K; Istajib Kulla Himmy Azz; Jaka Suwita; Sucipto Basuki (Paradigma Mandiri : Jurnal Pengabdian Kepada Masyarakat, 2025)
Waru Brilliant Thematic Village, Bojong Renged, Teluk Naga District, Tangerang Regency, is one of the best thematic villages that has received a grant from Bank Indonesia (BI) in 2024. The grant in the form of an appropriate tool aims to improve community welfare, food security, and the local economy. Universitas Insan Pembangunan Indonesia (UNIPI) facilitates and moderates this activity, including training on the use of tools and assistance in their implementation. This activity aims to evaluate the effectiveness of grants in improving community welfare. The evaluation results show that the appropriate tools have been well adopted and provide significant benefits to increase production and food security in the region.